Microwave assisted rapid synthesis of 4-amino-3,4-dihydroquinolin-2-ones from azetidin-2-ones - Shirode, N. M.; Kulkarni, K. C.; Gumaste, V. K.; Deshmukh, A. R. A. S. (Arkivoc, 2005)
An efficient one-pot synthesis of 4-amino-3,4-dihydroquinolin-2-ones from 3-(2-nitrophenyl)-1, 4-disubstituted azetidin-2-ones is described. Microwave assisted transfer hydrogenation of a nitro group followed by in situ beta-lactam ring opening by the newly formed amino group is the key step in this synthesis.
Keywords: 4-amino-3; 4-dihydroquinolin-2-ones; azetidin-2-ones; imines; ketenes; Microwave; transfer hydrogenation